Formal Total Syntheses of (+)‐ and (–)‐ar‐Macrocarpene via Rh(I)‐BINAP Catalyzed Conjugate Addition. Issue 16 (15th April 2020) - Khatua, Arindam; Pal, Souvik; Bisai, Vishnumaya
Abstract : Catalytic asymmetric formal total syntheses of both antipodes of sesquiterpene, (+)‐ ar ‐macrocarpene (1 ) and (–)‐ ar ‐macrocarpene ( ent ‐1 ) has been achieved from 5, 5‐dimethyl‐(3‐ p ‐tolyl)cyclohexanone 12 . Enantioenriched compound 12 was obtained in excellent yield with 96 % ee by catalytic enantioselective p ‐tolylboronic acid addition to 5, 5‐dimethyl cyclohexen‐2‐one 13 using Rh (I) ‐( S )‐BINAP (L7 ). Moreover, ent ‐12 was achieved in 96 % ee by using Rh (I) ‐( R )‐BINAP ( ent ‐L7 ). Abstract : Formal Total syntheses of both the enantiomers of ar ‐Macrocarpene has been described via a key Rh (I) ‐BINAP catalyzed p ‐tolyl boronic acid addition to substituted 2‐cyclohexenone (up to 94 % yield and 96 % ee ). Rh (I) ‐( S )‐BINAP provided intermediate ( S )‐5, 5‐dimethyl‐3‐( p ‐tolyl)‐cyclohexanone for naturally occurring (+)‐ ar ‐Macrocarpene, whereas the antipode of catalyst, Rh (I) ‐( R )‐BINAP afforded ( R )‐5, 5‐dimethyl‐3‐( p ‐tolyl)‐cyclohexanone for the synthesis of unnatural enantiomer, (–)‐ ar ‐Macrocarpene.